Surveying noctural cuttlefish camouflage behaviour using an AUV - Williams, S.B.; Pizarro, O.; How, M.; Mercer, D.; Powell, G.; Marshall, J.; Hanlon, R. (2009 IEEE International Conference on Robotics and Automation, 2009)
This paper describes a recent study in which an autonomous underwater vehicle (AUV) with a high resolution stereo-imaging system was used to document nocturnal camouflage behaviour in cuttlefish at a well known spawning site in Whyalla, South Australia. The AUV's ability to fly at low altitude during day and night while closely following a desired survey pattern provided improved data collection compared to divers and previous work with a small ROV. Over the course of the week long expedition, the AUV Sirius was deployed on 38 dives at three sites in the survey area and collected tens of thousands of stereo images. Of these, nearly a thousand were seen to contain cuttlefish during post cruise analysis, with a large proportion showing evidence of camouflage. The distribution of images containing cuttlefish suggest that the animal concentrations were substantially higher closer in to shore in shallow waters, where the flat rocky substrate occurs; females lay their eggs on the underside of these rocks. Results demonstrate the strengths of using an AUV for surveying near-shore benthic habitats of ecological interest, with a particular emphasis on the ability to operate during both day and night time operations.